Analisis Sistem Informasi Manajemen pada Pengelolaan Data Santri di Pondok Pesantren - Najwatul Masruroh; Siti Nur Khotimah; Supriyati Ningsih; Wardatus Safira; Yeni Tri Nur Rahmawati (CV. Lentera Literasi Indonesia, 2026)
Santri (student) data management in Islamic boarding schools (pondok pesantren) often faces challenges such as data redundancy, slow information retrieval, and the risk of physical document loss. This study aims to analyze the implementation of Management Information Systems (MIS) in managing santri data to improve the efficiency, accuracy, and integration of academic and administrative information. The research method employed is descriptive qualitative with a system analysis approach using the PIECES framework or SWOT analysis. Data collection was conducted through observation, interviews, and documentation studies at the pondok pesantren. The results indicate that the transition from a conventional system to a digital-based MIS can significantly reduce data processing time, facilitate reporting to santri's parents or guardians, and support decision-making by the boarding school leadership. However, the main constraints encountered include limited IT infrastructure and the readiness of human resources (operators). This study concludes that MIS implementation is highly crucial for the modernization of pesantren, yet it requires management commitment in continuous human resource training.